Integrated Flood Risk Mapping and Hazard-Vulnerability Assessment for Mitigation Prioritization in Sumatra - Hasan Adi Nugraha; M. Angga Hadi Pratama; Muhammad Alsamtu Tita Sabila Pratama Suhartono; Anjar Dimara Sakti; Ketut Wikantika (Geoplanning: Journal of Geomatics and Planning, 2026)
Flood risk in tropical regions such as Sumatra is increasing due to intensified rainfall extremes and rapid urbanization. Although flood hazard mapping is widely applied, many studies do not clearly distinguish physical hazard from socio-economic vulnerability, limiting their usefulness for targeted mitigation. This study proposes an integrated geospatial framework combining multi-parameter flood hazard assessment and a socio-demographic vulnerability index through a bivariate hazard–vulnerability matrix to support risk reduction. The framework was applied to the November 2025 flood events in Aceh, North Sumatra, and West Sumatra, using nine hazard parameters and four vulnerability indicators. Results show that High to Very High Hazard zones cover 21% of the study area, in lowland basins, while 12% of the area falls into the Very High-Risk category. Validation using observed damage data shows that medium-risk (Risk 2) zones, rather than only the highest-risk cores, account for 87.5%–100% of the exposed population across five major cities, capturing 97.5% of affected residents in Aceh Tamiang. The proposed 5×5 bivariate matrix separates risk dominated by physical hazard, socio-economic vulnerability, or their interaction This enables stratified mitigation strategies, ranging from integrated structural and social interventions to targeted engineering and community-based measures, while providing spatially explicit guidance to strengthen flood risk management and support Sendai Framework objectives under climate change.